Dating the first New Zealanders : the chronology of Wairau Bar - Higham, Thomas
The first colonization of New Zealand is a much debated issue. The lack of appropriate absolute dating has meant chronology has been poorly understood. New 14C dating of materials from archaic Polynesian graves and occupation levels provides important precision and understanding of early exploitation on New Zealand.